“Diseño e implementación de un módulo didáctico de ciclo conversores monofásicos y trifásicos para la visualización de las formas de onda”. - Caiza Galarza, Kathya Geovanna (2024)
The study of power electronics subject has a great importance because it allows technological progress in the conversion of electrical energy into different applications supported by semiconductor elements, using and taking advantage of this theoretical principle for the creation and innovation of new technology. The lack of new innovative equipment for the Electrical Machines laboratory of the Electromechanical Engineering career at the Technical University of Cotopaxi does not enable students to visualize in real time the waveforms in the converter cycle of electrical magnitude of voltage in single-phase and three-phase systems. This degree project is focused on the design and implementation of a didactic module of single-phase and three-phase cycle converters for the visualization of the waveforms, through a field analysis and design of circuits with Proteus and Arduino software support. For the development of the didactic module, the principal aspect was to establish the voltage and current parameters to be manipulated for later simulation and programming of the mentioned software and after that the selection of appropriate semiconductor elements that fulfill the desired parameters. Concluding with the operation tests and visualization of the voltage waveforms in real time with an electrical noise of 2V in the analog-digital converter, considering an error of 5% in the simulation and measurement of the output voltage in a theoretical and practical manner.